A dynamic multilevel ecological approach to drinking event modelling and intervention. (25th June 2020) - Gonzalez Villasanti, Hugo; Madden, Danielle; Passino, Kevin; Clapp, John
Abstract: The complex and dynamic interplay between an individual's psychophysiological processes and multilevel interactions with his/her group and environment during alcohol drinking events is analysed in this work. Our aim is to provide a system dynamics model to accurately represent a drinking event and provide guidelines for feedback‐based behavioural interventions. We employ a pharmacodynamics model of alcohol metabolism, with a self‐regulation approach of decision‐making to characterize the individual's drinking behaviour. The nonlinearities introduced by the acute effects of alcohol in cognition, along with social perception and influence, complete the individual's model, which serves as a basis for the group and environment's behaviour models. A sensitivity analysis revealed that influenceability and overestimation via descriptive social norms are key drivers of higher blood alcohol content levels. Furthermore, simulations showed that intervening early in the event, before cognition processes are inhibited, and targeting groups of individuals result in efficient implementations.